Leadership for family and community involvement - Houston, Paul D.; Blankstein, Alan M., 1959-; Cole, Robert W., 1945- (Thousand Oaks, Calif. : Corwin Press ; [Bloomington, Ind.] : Hope Foundation ; [Arlington, Va.] : American Association of School Administrators, 2010)
Includes bibliographical references and index.